Tanggung Jawab Hukum Kurator Atas Pengurusan Dan Pemberesan Harta Pailit - Herlina, Herlina; Abbas, Ilham; Risma, Andi (Qawanin Jurnal Ilmu Hukum, 2022)
ABSTRAC This study aims to determine and analyze the legal responsibility of the curator in managing and resolving bankruptcy assets and to find out and analyze the sanctions for the curator if there is an error or negligence in his responsibility. In this legal research the writer uses a normative legal approach. In the normative legal approach, only library materials or secondary data are studied, which include primary and secondary legal materials. By conducting studies and analysis of legal protection for curators against creditor; lawsuits in the management and settlement of bankruptcy assets in terms of literature and Law No.37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The results of this study illustrate that the curator is personally responsible and the curator must payfor the losses it incurs by himself, where this responsibility can occur, for example, if the curator embezzled bankruptcy assets and any losses incurred, as a result of negligence or due to unprofessionalism of the curator becomes the responsibility of the curator , therefore, the loss cannot be borne by the bankruptcy estate. As a suggestion It is better if the curator in managing and resolving bankruptcy assets, the curator should carry out his duties carefully and professionally. Regarding the demands that can be given to the curator, demands may be made if the curator carries out his responsibilities deviating from the provisions of laws and other regulations. ABSTRAK Penelitian ini bertujuan Untuk mengetahui dan menganalisis Tanggung Jawab Hukum Kurator dalam pengurusan dan pemberesan harta pailit dan Untuk mengetahui dan menganalisis sanksi bagikurator apabila terdapat kesalahan atau kelalaian dalam tanggung jawabnya. Dalam penelitian hukum ini penulis menggunakan pendekatan hukum normatif. Pada pendekatan hukum normatif yang diteliti hanya bahan pustaka atau data sekunder, yang mencapkup bahan hukum primer dansekunder. Dengan melakukan pengkajian dan analisis terhadap perlindungan hukum bagi kurator terhadap tuntutan hukum kreditur dalam pengurusan dan pemberesan harta pailit ditinjau dariberbagai Literatur dan Undang-Undang No.37 Tahun 2004 Tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang. Hasil Penelitian ini menggambarkan kurator bertanggung jawab secara pribadi dan kurator harus membayar sendiri kerugian yang ditimbulkannya, dimana tanggung jawab ini dapat terjadi, misalnya, jika kurator menggelapkan harta kepailitan dansegala kerugian yang timbul, sebagai akibat dari kelalaian atau karena ketidakprofesionalan kurator menjadi tanggung jawab kurator, oleh karenanya kerugian tersebut tidak bisa dibebankanpada harta pailit. Sebagai Saran Sebaiknya kurator dalam pengurusan dan pemberesan harta pailit kurator melaksanakan tugasnya dengan teliti dan profesional. Mengenai tuntutan yang dapat diberikan kepada kurator, tuntutan bisa saja diberikan jika kurator melaksanakan tanggungjawabnya melenceng dari ketentuan Undang-undang dan peraturan lain.